2022
DOI: 10.1016/j.annonc.2022.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell DNA-seq depicts clonal evolution of multiple driver alterations in osimertinib-resistant patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Analysis of the single-cell DNA sequencing of the NSCLC cohort enrolled in the MATCH-R (NCT0251782) trial that developed osimertinib resistance revealed heterogeneity of acquired mutations in the cells including FGFR3-TACC3, KIF5B-RE , and STRN-ALK fusions that can be treated by existing drugs, thus suggesting possible treatments to overcome osimertinib resistance. 252 Similarly, RNA sequencing revealed that ALK junctional heterogeneity in NSCLC may predict resistance to crizotinib. 253 Likewise scRNA-seq of chemoresistant cervical cancer revealed induction of the (PI3K)/AKT pathway.…”
Section: Experimental Methods For Identification Of Fusion Oncogenesmentioning
confidence: 99%
“…Analysis of the single-cell DNA sequencing of the NSCLC cohort enrolled in the MATCH-R (NCT0251782) trial that developed osimertinib resistance revealed heterogeneity of acquired mutations in the cells including FGFR3-TACC3, KIF5B-RE , and STRN-ALK fusions that can be treated by existing drugs, thus suggesting possible treatments to overcome osimertinib resistance. 252 Similarly, RNA sequencing revealed that ALK junctional heterogeneity in NSCLC may predict resistance to crizotinib. 253 Likewise scRNA-seq of chemoresistant cervical cancer revealed induction of the (PI3K)/AKT pathway.…”
Section: Experimental Methods For Identification Of Fusion Oncogenesmentioning
confidence: 99%
“…Tumors can show two or more resistance mechanisms, such as focal copy-number amplifications in MET, KRAS, and PD-L1, gene fusions of ALK, MKRN1-BRA, and ESR1-AKAP12, as well as neuroendocrine differentiation [153]. Therefore, combination therapy strategies have been strongly indicated in these cases [154].…”
Section: Clonal Evolution and Tumor Heterogeneity Within Mrdmentioning
confidence: 99%
“…[171][172][173] The combination of TKIs and inhibitors of downstream molecules or chemotherapeutic agents can effectively mitigate drug resistance. 174 Administration of multitargeted TKIs and combinations of different TKIs are more effective. For instance, cabozantinib is an oral multikinase inhibitor targeting VEGFR1/2/3, MET, and AXL and has an acceptable efficacy in patients with advanced HCC and GIST.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%